Local government in Ethiopia : advancing development and accommodating ethnic minorities - Zemelak Ayitenew Ayele (Baden-Baden :. : Nomos Verlagsgesellschaft, 2014)
This study inquires into whether the regional states are discharging their constitutional obligation of creating adequately empowered local government. It will attempt to do so by examining the decentralisation programme of four of the nine regional states of the Ethiopian federation.
Introduction -- Designing local government for development and accommodation of diversity -- Local administration, development, and ethnicity in Ethiopia : historical perspective -- Decentralisation within Ethiopia's federation : constitutional basis and political motives -- Decentralisation and development in Ethiopia : local autonomy -- Decentralisation and development in Ethiopia : central supervision and inter-governmental co-operation -- Decentralisation and accommodation of intra-regional ethnic minorities in Ethiopia -- Conclusion.
Ethiopia has adopted a system of devolution to local government, within a federal system, as a strategy to advance development and to manage the ethnic diversity of its people. Ethiopia's local governments, i.e. its woredas, kebeles and zones are posited as critical to achieving developmental ends and to accommodate the country's ethnic diversity. This book examines whether the institutional design underlying these local governments enables them to achieve these objectives. Based on international literature, the book identifies institutional features that are critical to enhance the potential of local government to advance development and accommodate ethnic minorities. In light of these institutional features the book presents a comprehensive description and analysis of the policies and laws surrounding local government in Ethiopia. It draws lessons, both negative and positive, relevant for other African countries with the same twin challenge of development and accommodating ethnic diversity.
Includes bibliographical references (pages 329-355)
Keywords: Local government -- Ethiopia; Local government -- Law and legislation -- Ethiopia; Local government -- State supervision -- Ethiopia; Local government..; Local government -- Law and legislation..; Local government -- State supervision..; Ethiopia..